2014
DOI: 10.1155/2014/371087
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Decitabine-Based Chemoimmunotherapy for Patients with Refractory Advanced Solid Tumors: A Phase I/II Report

Abstract: Aberrant DNA methylation is one of the main drivers of tumor initiation and progression. The reversibility of methylation modulation makes it an attractive target for novel anticancer therapies. Clinical studies have demonstrated that high-dose decitabine, a hypomethylating agent, results in some clinical benefits in patients with refractory advanced tumors; however, they are extremely toxic. Low doses of decitabine minimize toxicity while potentially improving the targeted effects of DNA hypomethylation. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…This clinical trial showed a favorable PFS and clinical response without a significant increase in toxicity. Our previous clinical trials of low‐dose decitabine in other tumors exhibited the similar findings 12, 28…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This clinical trial showed a favorable PFS and clinical response without a significant increase in toxicity. Our previous clinical trials of low‐dose decitabine in other tumors exhibited the similar findings 12, 28…”
Section: Discussionsupporting
confidence: 75%
“…However, it is becoming increasingly clear that the impact of epigenetics on both the tumor cell and the tumor microenvironment plays a critical role in the development of drug resistance 9, 10, 11. Consistent with this hypothesis, previous laboratory and clinical data suggest that an epigenetic strategy may overcome chemotherapy resistance and mediate a return to a baseline state of treatment susceptibility in various cancers 11, 12, 13, 14, 15. Epigenetic perturbations, particularly hypomethylating agents (HMA), re‐sensitize cancer cells to chemotherapy presumably by resetting the epigenetic infrastructure and altering gene expression in the tumor 16, 17, 18.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, they have been recognized as having lower toxicity compared to traditional chemotherapy. In fact, low-dose treatment of Aza-dC in patients with MDS [108] and solid tumors [109] resulted in complete response of the patients. Thus using low-dose DNA methylation inhibitors may provide a safe therapeutic choice [65] especially for elderly patients [107,110] .…”
Section: Resultsmentioning
confidence: 99%